Depression, anxiety and suicidal ideation among 1st and 2nd generation migrants - results from the Gutenberg health study. Issue 1 (December 2016) - Beutel, Manfred; Jünger, Claus; Klein, Eva; Wild, Philipp; Lackner, Karl; Blettner, Maria; Banerjee, Mita; Michal, Matthias; Wiltink, Jörg; Brähler, Elmar
Abstract Background Even though migrants constitute a large proportion of the German population, there is a lack of representative studies on their mental health. Hence, the present study explored mental health characteristics and suicidal ideation comparing 1st and 2nd generation migrants to non-migrants and subgroups within 1st generation migrants. Methods We investigated cross-sectional data of 14, 943 participants of the Gutenberg Health Study (GHS), a population-based, prospective, single-center cohort study in Mid-Germany (age 35 to 74 years). Migration status was assessed according to the German microcensus criteria. Depression and anxiety were measured by the PHQ (PHQ-8, GAD-2, Panic module), social anxiety by the Mini SPIN and Distressed Personality (Type D) by the DS-14. Suicidal ideation was assessed by the single item of the PHQ-9. Results A total ofn  = 3, 525 participants had a migration background; the proportion of 1st generation (immigrated after 1949) migrants was 10.6 % (2nd generation 13 %). Among the 1st generation migrants those with Polish (N  = 295) and Turkish (N  = 141) origins were the largest groups from single countries. Controlling for sex, age and socioeconomic status, 1st generation migrants reported significantly more depression (OR 1.24; CI 1.01-1.52), generalized anxiety (OR 1.38; CI 1.13-1.68), panic attacks in the past 4 weeks (OR 1.43; CI 1.16-1.77); Type D (OR 1.28; CI 1.13-1.45) and suicidal ideation (1.44; CI 1.19-1.74) compared to non-migrants. The mental health of 2nd generation migrants did not differ from native Germans; they had the highest socioeconomic status of the three groups. Compared to native Germans, Turkish migrants of both sexes reported more depression and panic, particularly a strongly increased suicidal ideation (OR 3.02; CI 1.80-5.04) after taking sex, age, and socioeconomic status into account. Polish migrants only reported an increased rate of suicidal ideation and Type D. Turkish migrants exceeded Polish migrants regarding depression (OR = 2.61; 95 % CI 1.21-5.67), and panic attacks (OR=3.38; 95 % CI 1.45-7.85). In the subgroup analyses years lived in Germany was not significant. Conclusions One of few representative community studies shows that compared to native Germans depression, anxiety and suicidal ideation were more frequently reported by 1st generation migrants, particularly of Turkish origin. Overall, 2nd generation migrants appear to have adjusted successfully. Limitations refer to a lack of data for persons without German language skills and missing mental health data in the Turkish sample. Further analyses need to address causes of mental strains and health care needs and provision.